Innovative insight: ChatGPT’s contribution to advanced health research articles - Muslim, M. Rifqi Fadillah; Chabib, Lutfi; Hamzah, Hasyrul; Santosa, Agus (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2023)
The current technological advancement follows a pattern of both disruptive and gradual changes. The field of communication is currently the most extensively utilized technology. The rapid development of AI has enabled those without a background in computer coding or specialized health knowledge to utilize this technology, which gives rise to numerous issues. This phenomenon elicits curiosity and engenders debate among the general public, scholars, healthcare providers, and researchers in the health industry. Utilizing AI in the composition of scientific publications necessitates explicit norms and regulations, a robust validation procedure, and effective collaboration between AI systems and human expertise. Ensuring transparency and acknowledgment of AI usage is crucial to maintaining human researchers’ accountability for the ultimate outcomes of their research.